Pengaruh Lingkungan Kerja Dan Stres Kerja Terhadap Kinerja Karyawan Pada PT Xing Hao Technology Kota Tangerang - Rahma Solikhati Hidayah; Muhammad Gandung (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. This research aims to find out how much influence the work environment has on the performance of PT employees. Xing Hao Technology Tangerang City, to find out how much influence work stress has on the performance of PT employees. Xing Hao Technology Tangerang City to find out how much influence the work environment and work stress have on the performance of PT employees. Xing Hao Technology Tangerang City. The population of this study used a Slovin sample of 70 people. Data was collected through a questionnaire distributed using Google Forms, this research uses quantitative methods. The research results show that, partially, work environment variables have a significant effect on employee performance by showing the test results tcount = 7.242 while ttable = 1.99601 (tcount > ttable) with a significance level of 0.000. Partially, the work stress variable has a significant effect on employee performance by showing the results of tcount = 2.047 while ttable = 1.99601 (tcount > ttable) with a significance level of 0.045. Simultaneously, work environment variables and work stress have a significant effect on employee performance by showing Fcount = 185.460 which is greater than Ftable = 3.13 with a significance of 0.0000. So it can be said that the work environment and work stress simultaneously have a significant effect on the performance of PT employees. Xing Hao Technology Tangerang City